VD_FINDINFO Décision / 2011 / 776 vom 21. Dezember 2011 - VD Tribunal cantonal (2011)
DÉTENTION PRÉVENTIVE, RISQUE DE FUITE | 221 al. 1 let. a CPP (CH), 222 CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)